1995
DOI: 10.1006/dbio.1995.0011
|View full text |Cite
|
Sign up to set email alerts
|

Effect on Sperm-Induced Activation Current and Increase of Cytosolic Ca2+by Agents That Modify the Mobilization of [Ca2+]i

Abstract: The mechanism of the elevation of intracellular free Ca2+ ([Ca2+]i) induced by a single sperm in eggs of the sea urchin Lytechinus variegatus was investigated. Simultaneous measurements of [Ca2+]i, and of the activation current, were carried out on eggs microinjected with Ca Green-1 or Ca Green dextran, and voltage clamped at -20 mV. The microinjection of 0.5 to 1.0 mg/ml heparin (MW 6000) or pentosan polysulfate (MW 3000), final intracellular concentration, causes a concentration-dependent inhibition in all p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
58
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 0 publications
14
58
0
Order By: Relevance
“…3a) and the cortical exocytosis reaction (not shown) previously documented by others (22)(23)(24). The height of the peak produced by Ins-P 3 reached a maximum of 1.2 arbitrary units, the Ca 2ϩ increase lasting about 7 min.…”
Section: Resultssupporting
confidence: 68%
“…3a) and the cortical exocytosis reaction (not shown) previously documented by others (22)(23)(24). The height of the peak produced by Ins-P 3 reached a maximum of 1.2 arbitrary units, the Ca 2ϩ increase lasting about 7 min.…”
Section: Resultssupporting
confidence: 68%
“…Studies have shown that microinjection of the InsP 3 receptor antagonist heparin in conjunction with antagonists of the ryanodine receptor, such as ruthenium red and the cADPR inhibitor 8-amino-cADPR, block the Ca 2ϩ transient at fertilization (10,11). Injection with heparin alone, unless used at relatively high concentrations (12), does not abolish the fertilization Ca 2ϩ transient (10,11,13). cADPR and ryanodine receptor antagonists block the transient only in the presence of InsP 3 antagonists (10,11), if at all (14).…”
mentioning
confidence: 99%
“…InsP 3 is produced by members of the phosphatidylinositol phospholipase C (PLC) enzyme family and has been shown to be generated at fertilization (15)(16)(17)(18). Chemical inhibitors of PLC, pentosan polysulfate and U73122, can abolish fertilization Ca 2ϩ transients in sea urchin eggs (12,17). Molecular inhibition studies, using dominant negative PLC␥SH2 domain constructs, show that sperm-activated Ca 2ϩ release and egg activation are markedly delayed, then blocked, when activation of this enzyme is inhibited (19 -21).…”
mentioning
confidence: 99%
“…The time of increase in ΔΨ m was also close to the value already mentioned using simultaneous measurements of ΔΨ m and [Ca 2+ ] i . The rise time of ΔNO, 53.5 s, has been previously reported around a peak of [Ca 2+ ] i by the method of simultaneous measurement of ΔNO and the activation current (AC) in a voltage-clamped egg because a peak of AC that corresponds to a peak of [Ca 2+ ] i (Mohri et al 1995 ;Mohri et al 2008 ).…”
Section: Timing Of δψ M and δNomentioning
confidence: 81%